Integrated Diabetic Clinic in a Rural Hospital of Nepal - Thapa, Niresh; Maharjan, Muna (Journal of Karnali Academy of Health Sciences, 2019)
Diabetes is an important public health concern which is increasing rapidly in developing countries. It is challenging to prevent and manage diabetes in a rural setting. The Integrated Diabetic Clinic is comprehensive diabetes care under one roof. Its aim is to provide efficient accessible and affordable comprehensive care. It will make a huge difference in the management of diabetes. This clinic will play a major role in unifying different aspects of health care under one roof and offer the most comprehensive and cost-effective accessible health care to minimize mortality and morbidity associated with diabetes.